Ubezpieczenia na życie w Polsce jako jeden z elementów III filaru nowego systemu ubezpieczeń społecznych - Stęplewska, Kinga (Life insurance in Poland as one of the element in third pillar new pensions system, 2006)
The changes in the Polish pensions system, initiated by the law in 1999, have divided new system into three pillars: two obligatory, one optional. In the reformed Polish system – life insurance with an investment fund supplement the performance from two obligatory pillars. The article presents life insurance products which let employee invests money in his/her old age. The State supports Employee Pensions Schemes as group insurance, but all citizens can buy individual product, too. On the one hand it’s chance for employees, who know that pension from two obligatory pillars will be not enough, on the other hand for insurance companies to expansion of their firms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 516-523